Immuno-protective impact and clinical translation of radioprotective agents in cancer radiotherapy - Huang, Yiyong; Lv, Xiaolan; Si, Tao; Meng, Xia; Liao, Xiaolin; Zhang, Pengfei; Peng, Zheng; Zhou, Zheyi; Yi, Ping; Huang, Shigao (Frontiers in Immunology, 2025)
Radiotherapy, as a key component of the comprehensive treatment system for malignant tumors, not only facilitates precise tumor destruction but also necessitates the strategic use of radioprotective agents to regulate immune responses and mitigate toxicity in normal tissues. Revealing the molecular biological mechanisms of ionizing radiation damage, such as DNA double-strand breaks, oxidative stress responses, and abnormal cell cycle regulation is critical for the development of clinically effective radioprotective drugs. Such advancements hold dual significance in enhancing patient outcomes and improving clinical efficacy. This paper explores the classification of radioprotective agents, and their diverse mechanisms of action, including free radical scavenging, regulation of redox enzyme systems, suppression of ionizing radiation-induced inflammation, and apoptosis-related immune damage. And, it also examines the challenges and prospects of their clinical translation. This study aims to provide important theoretical framework for the development of radioprotective agents to contribute to future advancements in radiation therapy.